MOTIVASI FAKTOR YANG MEMPENGARUHI MOTIVASI KESEDIAAN MASYARAKAT MENERIMA VAKSIN COVID 19: FAKTOR YANG MEMPENGARUHI MOTIVASI KESEDIAAN MASYARAKAT MENERIMA VAKSIN COVID 19 - Dian Nur Adkhana Sari; Yeni Isnaeni (STIKES Pemkab Purworejo, 2023)
Background At the beginning of 2019 the outbreak of the covid 19 virus, transmission through respiratory droplets. The number of cases continues to increase from time to time. WHO data obtained that in 2021 there were 238,521,855 confirmed cases of Covid-19, including 4,863,818 deaths. Efforts to reduce the incidence of Covid-19 are by vaccinating. The problem with giving vaccines is resistance from the community. There are several factors that influence people's motivation to do vaccines, including the level of knowledge, perceptions, family support, support for health workers, attitudes and beliefs. The aim of the research is to know the factors that influence the motivation for the availability of the Covid-19 vaccine. The method of this type of research is quantitative with a cross sectional study design. Using the Kendall Tau and Chi Square tests. The population in this study were residents of the village of Agrasmanis, Jenawi sub-district, Karanganyar Regency, Central Java, with a total of 3,126 people. The sampling technique using simple random sampling was obtained as many as 312 people. Instrument using a questionnaire. The results showed that the factors influencing the motivation of people's willingness to accept vaccines included attitudes, beliefs, family support, support from health workers, level of knowledge and perceptions with a p-value of 0.000. Keywords: motivation, attitude, belief, family support, health worker support, level of knowledge and perception